Structural basis for inhibition of 17β-hydroxysteroid dehydrogenases by phytoestrogens: The case of fungal 17β-HSDcl. Issue 171 (July 2017) - Cassetta, Alberto; Stojan, Jure; Krastanova, Ivet; Kristan, Katja; Brunskole Švegelj, Mojca; Lamba, Doriano; Lanišnik Rižner, Tea
Graphical abstract: Highlights: Kinetics and crystallography reveal mechanism of 17β-HSDcl inhibition by flavonoids. Flavonoids are competitive inhibitors of 17β-HSDcl, with low micromolar Ki . OH-7 on the chromone moiety and flavonol hydrophobicity are critical for inhibition. Methylation of OH-4′ of isoflavones strongly influences their inhibitory activity. Abstract: Phytoestrogens are plant-derived compounds that functionally and structurally mimic mammalian estrogens. Phytoestrogens have broad inhibitory activities toward several steroidogenic enzymes, such as the 17β-hydroxysteroid dehydrogenases (17β-HSDs), which modulate the biological potency of androgens and estrogens in mammals. However, to date, no crystallographic data are available to explain phytoestrogens binding to mammalian 17β-HSDs. NADP(H)-dependent 17β-HSD from the filamentous fungus Cochliobolus lunatus (17β-HSDcl) has been the subject of extensive biochemical, kinetic and quantitative structure–activity relationship studies that have shown that the flavonols are the most potent inhibitors. In the present study, we investigated the structure–activity relationships of the ternary complexes between the holo form of 17β-HSDcl and the flavonols kaempferol and 3, 7-dihydroxyflavone, in comparison with the isoflavones genistein and biochanin A. Crystallographic data are accompanied by kinetic analysis of the inhibition mechanisms for six flavonols (3-hydroxyflavone, 3, 7-dihydroxyflavone, kaempferol, quercetin, fisetin, myricetin), one flavanone (naringenin), one flavone (luteolin), and two isoflavones (genistein, biochanin A). The kinetics analysis shows that the degree of hydroxylation of ring B significantly influences the overall inhibitory efficacy of the flavonols. A distinct binding mode defines the interactions between 17β-HSDcl and the flavones and isoflavones. Moreover, the complex with biochanin A reveals an unusual binding mode that appears to account for its greater inhibition of 17β-HSDcl with respect to genistein. Overall, these data provide a blueprint for identification of the distinct molecular determinants that underpin 17β-HSD inhibition by phytoestrogens.